Strategic approach to analyze the effect of Covid-19 on the stock market volatility and uncertainty: A first and second wave perspective - Emon Kalyan Chowdhury (Journal of Capital Markets Studies (JCMS), 2022)
Purpose: This paper aims to analyze the impact of Covid-19 on the stock market volatility and uncertainty during the first and second waves. Design/methodology/approach: This study has applied event study and autoregressive integrated moving average models using daily data of confirmed and death cases of Covid-19, US S&P 500, volatility index, economic policy uncertainty and S&P 500 of Bombay Stock Exchange to attain the purpose. Findings: It is observed that, during the first wave, the confirmed cases and the fiscal measure have a significant impact, while the vaccination initiative and the abnormal hike of confirmed cases have a significant impact on the US stock returns during the second wave. It is further observed that the volatility of Indian and US stock markets spillovers during the sample period. Moreover, a perpetual correlation between the Covid-19 and the stock market variables has been noticed. Research limitations/implications: At present, the world is experiencing the third wave of Covid-19. This paper has considered the first and second waves. Practical implications: It is expected that business leaders, stock market regulators and the policymakers will be highly benefitted from the research outcomes of this study. Originality/value: This paper briefly highlights the drawbacks of existing policies and suggests appropriate guidelines to successfully implement the forthcoming initiatives to reduce the catastrophic impact of Covid-19 on the stock market volatility and uncertainty.
Keywords: B26; C58; E44; 330; Covid-19; Stock market; Economic uncertainty; Event study; ARIMA